Synthesis and Numerical Analysis of Compliant Devices: A Topology Optimization Approach for Mechanisms and Robotic Systems - S. Premanand; G. Arunkumar; Venkatesa Prabhu Sundramurthy (Advances in Materials Science and Engineering)
The topology optimization design invariably shall be used in various applications such as four bar mechanisms, robotics designs, aircraft engineering designs, and many other mechanical innovative systems for improving the efficiency in the system. This research paper emphasizes more on general topology optimization design for a rectangular domain in which numerically analyzed with defined boundary conditions. Furthermore, the same setting geometry has been taken for sensitivity analysis to find the objective stress and nonstress zones. Then, the geometry is topology optimized to analyze stress, safety factor, output deflection, and mass reduction. Also this research work focuses more on topology optimization, design synthesis, and objective function comparison in different materials. Hence, the results are suitable volume and mass reduction in various robotic devices. Validation and comparison of compliance base materials will further support the paper to extend the work for experimental analysis. This final topology optimized and validated device can be manufactured and forced to experimental fatigue endurance test cycle test condition in static and dynamic state. The results outshoot the final destination of this optimization design.